DEMOGRAPHIC DETERMINANTS OF ATTRITION OF TECHNICAL HUMAN RESOURCES- A STUDY OF THEINFORMATION TECHNOLOGY INDUSTRY IN INDIA - Khan, M. Basheer Ahmed (The International Journal of Accounting and Business Society, 2014)
The Information Technology Industry is the fastest growing Industry in India as well as the most contributing Industry to the Indian Economy. Needless to mention that the growth and contribution of the Industry can be sustained only if the workforce, especially the technical human resources of the industry remain stable. Unfortunately, with the sudden growth of the industry in India as well as the global competition unleashed, the environment posed great challenges to the industry by way of growing attrition. The industry faced attrition of its technical human resources to the extent of 30-40% half a decade ago and it continues to be near 15-20% in 2014. It kindled interest in academics to investigate the phenomenon and in this study, an attempt has been made to analyze the empirical data relating to the demographic determinants of attrition of technical human resources of the information technology industry in India. The paper investigates if the demographic factors like gender, age, educational qualifiations inflence their intentions to quit the fims or continue to stay. The fidings are signifiant with a view to evolving appropriate attrition management policies of the fims in the industry in India.